Magnetic and structural changes in LaCo0.9Mn0.1O3 at high pressure. (21st December 2017) - Capone, M; Ridley, C J; Funnell, N P; Stenning, G B G; Loveday, J S; Guthrie, M; Bull, C L
Abstract: The structural and magnetic properties of LaCo0.9 Mn0.1 O3 have been studied as a function of pressure by neutron powder diffraction and DC magnetometry. The material is confirmed to exhibit rhombohedral R 3 ̄ c symmetry between ambient pressure and 6 GPa. We have determined the bulk modulus B 0 of the sample using a second-order Birch–Murnaghan equation of state which yielded: B 0   =  140(9) GPa and V 0   =   112.7 ( 2 )   A ˚ 3 . We report a non-linear increase of the Curie temperature T C from an ambient pressure value of 224.7 K to  ̃236 K at a pressure of 4 GPa. Finally, we confirm the glassy-like nature of the magnetism in LaCo0.9 Mn0.1 O3, which is maintained throughout the pressure range explored.